LONGEVIDADE EMPRESARIAL: UM ESTUDO EM MICRO E PEQUENAS EMPRESAS DE SÃO BERNARDO DO CAMPO DO SETOR DE VAREJO - Moraes, Cláudio Zanutim (2014)
In Brazil, approximately 75 por cento off small business go bankrupt before two, three or even five years. This study analyzed ten companies microbusiness retail sector in the city of São Bernardo do Campo who are active and able to overcome and win the mortality business and marketing competition. The investigation was initiated by the ABC region, carrying out a survey in SEBRAE (Brazilian Service of Support for Micro and Small Enterprises) and JUCESP (Board of Trade of the State of São Paulo) to find the amount of micro and small enterprises that were active and that opened between 2006 and 2007. Later the focus was for the city of São Bernardo do Campo where they inaugurated 744 MSEs (Micro and Small Enterprises), and 49 of them were categorized in retail clothing and finally set up ten companies that met the pre-methodological requirements of the study. The discussion on the topic of business longevity, in other words, to understand what were the capabilities that some companies had to keep working for so many years was an essential factor for the study. The aim of this work was to check how to manage and treat their business where entrepreneurs who have made had survival on the market. This study drew on qualitative method of transversal cut with non-probability sample and quota in order to make the methodological process and build the final analysis of the research.